Factors affecting length of productive life and lifetime production traits in a commercial swine herd in Northern Thailand - Noppibool, Udomsak; Koonawootrittriron, Skorn; Elzo, Mauricio A.; Suwanasopee, Thanathip (Agriculture and Natural Resources, 2016)
The length of productive life (LPL) and lifetime production traits are economically important in commercial swine production systems. This study investigated factors that may influence the LPL and lifetime production traits of sows in a commercial swine population in Thailand. The dataset consisted of information from 2768 sows that had their first farrowing from 1989 to 2012. Three breed groups of sows were represented: 122 Duroc, 1944 Landrace and 702 Yorkshire. The traits analyzed were the LPL, lifetime piglets born alive (LBA), lifetime piglets weaned (LPW), lifetime piglets birth weight (LBW) and lifetime piglets weaning weight (LWW). The model consisted of year-season of first farrowing, breed group and age at first farrowing as fixed effects and the residual as a random effect. Year-season of first farrowing was an important source of variation for all traits (p < 0.0001). Yorkshire sows had the longest LPL (p < 0.05) and the highest LPW (p < 0.05) of all sow breed groups, whereas Duroc sows had the lowest least squares means for all traits. Landrace and Yorkshire sows had similar LBA, LBW and LWW. Thus, Yorkshire sows had the highest production efficiency (the longest LPL and highest LPW) of the three breed groups in this population. Age at first farrowing was negatively associated with LPL, LBA, LPW, LBW and LWW. The favorable association between age at first farrowing with LPL and LPW could be used to increase the efficiency of swine production in this population.